2005
DOI: 10.1021/tx050001a
|View full text |Cite
|
Sign up to set email alerts
|

Formation of 8-Oxo-7,8-dihydro-2‘-deoxyguanosine (8-Oxo-dGuo) by PAH o-Quinones:  Involvement of Reactive Oxygen Species and Copper(II)/Copper(I) Redox Cycling

Abstract: Polycyclic aromatic hydrocarbons (PAHs) are ubiquitous environmental pollutants and procarcinogens that require activation by host metabolism. Metabolic activation of PAHs by AldoKeto-Reductases (AKRs) leads to formation of reactive and redox active o-quinones, which may cause oxidatively generated DNA damage. Spectrophotometric assays showed that NADPH caused PAH o-quinones to enter futile redox-cycles, which result in the depletion of excess cofactor. Copper (II) amplified NADPH-dependent redox-cycling of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
87
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 75 publications
(89 citation statements)
references
References 48 publications
1
87
0
1
Order By: Relevance
“…PAH o-quinones produced by AKRs cause oxidative DNA damage in the form of 8-oxo-dGuo in vitro (30). However, whether 8-oxo-dGuo could be detected reliably as a result of PAH activation by AKRs in intact cells was unknown.…”
Section: Discussionmentioning
confidence: 99%
“…PAH o-quinones produced by AKRs cause oxidative DNA damage in the form of 8-oxo-dGuo in vitro (30). However, whether 8-oxo-dGuo could be detected reliably as a result of PAH activation by AKRs in intact cells was unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The electrophilic and redox active o-quinones can form a spectrum of DNA-adducts and evidence exists for stable bulky adducts formed by 1,4-Michael addition (which subsequently hydrate and cyclize) [68][69][70], the formation of depurinating DNA-adducts [71] , and the formation of 8-oxo-dGuo [72]. In vitro measurements of DNA-adduct formation suggest that the prominent lesions are those that result from oxidative damage of DNA [73].…”
Section: Poylcyclic Aromatic Hydrocarbonsmentioning
confidence: 99%
“…3,8) There is growing evidence that ROS have adverse effects on DNA and essential macromolecules. [8][9][10][11] Kumagai et al demonstrated that 9,10-phenanthrenequinone (9,10-PQ) is redox-active which can catalyze the transfer of electrons from dithiol to oxygen, generating superoxide. The consumption rate of thiol groups was proportional to the concentration of the catalytically active redox-active species in the sample.…”
Section: Introductionmentioning
confidence: 99%